Policy Uncertainty and Foreign Direct Investment: The Moderating Role of Institutional Quality - Akbakay, Zeki (Ekonomika, 2026)
This study investigates the impact of economic policy uncertainty (EPU) on foreign direct investment (FDI) inflows and examines how this relationship is moderated by institutional quality. The analysis is based on data from 37 developing countries over the period of 2002–2021. The World Uncertainty Index (WUI) and Worldwide Governance Indicators (WGI) serve as the primary data sources. Employing a two-step system Generalised Method of Moments (GMM) estimation for dynamic panel data, the study yields two key findings. First, policy uncertainty significantly reduces FDI inflows. Second, institutional quality – measured by the average of WGI dimensions – alleviates this negative effect. Robustness checks, including OLS estimation and analyses based on individual WGI components, confirm these results. Overall, the findings suggest that the adverse impact of policy uncertainty on FDI is conditional on the host country’s institutional strength; in countries with stronger institutions, FDI inflows are less susceptible to uncertainty.